(untitled) (Research, Society and Development, 2023)
The objective of this work was to estimate and present the normal climatological water balance (CWB) of municipalities located in different microregions of different mesoregions of Ceará. Four municipalities were selected: Barbalha, Guaramiranga, Morada Nova and Tauá, located in southern Ceará, North Ceará, Jaguaribe and Sertões cearenses, respectively. For the calculation of the CWB, the climatological normals of temperature and precipitation from 1991 to 2020 were used, available on the INMET website. The BHNC is very important for making available to irrigated agriculture the real conditions for an efficient management of water resources. The water balance was elaborated considering the available water capacity (CAD) of 100 mm. Based on the results obtained, the most critical periods were verified with water deficiency and the periods where water is most abundant in the system: The CWB revealed the need for soil water replacement for all the municipalities studied, especially Morada Nova and Tauá that presented water deficit practically in all months of the year. Guaramiranga presented the highest rainfall, therefore the lowest water deficit. Despite high rainfall, Barbalha presented water deficit between may and december. Based on the aridity index (AI) obtained from the CWB, Barbalha is sub-humid dry, Guaramiranga is sub-humid and humid, Morada Nova and Tauá have a semi-arid climate with water deficit throughout the year.